Preferensi Masyarakat Muslim Indonesia Terhadap Web Quality, E-Trust dan E- Purchase Intention Makanan Halal Online di Jepang - Yesi Elsandra; Yofina Mulyati; Tiara Turay; Nova Mustiqa (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2023)
This research is motivated by the needs of the Muslim community in Ishikawa Prefecture, Japan, for halal products. Given the limited availability of halal product distribution centers in countries with minority Muslim populations, recourse to online shopping platforms has emerged as a prominent avenue. It is noteworthy that these halal centers are predominantly concentrated in major urban areas such as Tokyo, Kyoto, and Osaka. To acquire halal products, the Muslim community visits halal online stores and effectively makes product selections through these websites. The research aims to investigate the influence of web quality, e-trust, and halal labeling on the purchase intention of the Muslim community in Ishikawa Prefecture, Japan. The research methodology adopted in this study involves a descriptive research design, anchored within a quantitative paradigm. The population for this study consists of the Muslim community in Kanazawa City, Japan. A sample of 32 respondents was selected using purposive sampling. The empirical findings of this study indicate that web quality, e-trust, and halal labeling have a significant impact on the purchase intention of the Muslim community in Ishikawa Prefecture, Japan. The coefficient of determination reveals that the combined influence of web quality, e-trust, and halal labeling significantly affects the purchase intention of the Muslim community in Ishikawa Prefecture, Japan. ABSTRAK Salah satu cara untuk mendapatkan produk halal di negara minoritas adalah dengan berbelanja melalui sistem online. Pusat kelengkapan produk halal umumnya hanya berada di kota besar seperti Tokyo, Kyoto, Osaka. Untuk mendapatkan produk halal, masyarakat Muslim akan mengunjungi website toko halal dan memilih produk melalui website tersebut. Tujuan penelitian untuk mengetahui Pengaruh web quality e-trust dan label halal terhadap Purchase Intention masyarakat Muslim di Provinsi Ishikawa, Jepang. Metode penelitian yang digunakan deskriptif dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah masyarakat Muslim di kota Kanazawa, Jepang. Sampel dalam penelitian ini berjumlah 32 responden yang diambil menggunakan metode purposive sampling. Hasil penelitian menunjukkan bahwa web quality, e-trust dan label halal berpengaruh signifikan terhadap Purchase Intention Masyarakat Muslim di Provinsi Ishikawa, Jepang. Hasil koefisien determinasi menunjukkan bahwa kontribusi pengaruh web quality, e-trust dan label halal berpengaruh terhadap Purchase Intention Masyarakat Muslim di provinsi Ishikawa.